2012
DOI: 10.5172/conu.2012.41.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Muslim person’s experiences of diabetes during Ramadan: Information for health professionals

Abstract: This phenomenological study provides an in-depth understanding of the lived experiences of Muslim persons with diabetes during Ramadan. The findings facilitate health professionals' knowledge of the unique needs of these clients during this time. van Manen's (1990) and Hycner's (1985) analytical methods assisted in producing the themes: knowing and understanding - being in harmony with the body, knowing its capabilities and limitations and its response to change; controlling - being in charge of diabetes durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The results from the group discussions echo previous findings related to the interface between formal care, the impact of the family and the community, beliefs and perceptions regarding fasting, religious influence, and managing blood glucose during Ramadan (Almansour et al, ; Gaborit et al, ; Lee et al, , ; Mygind, Kristiansen, Wittrup, & Nørgaard, ; Patel et al, ; Peterson et al, ). People with diabetes have been shown to fast despite their HCP advising against the practice (Chowdhury, Khan, Lasker, & Choudhary, ), and this was confirmed by the workshop participants when relating their experiences prior to DAFNE.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results from the group discussions echo previous findings related to the interface between formal care, the impact of the family and the community, beliefs and perceptions regarding fasting, religious influence, and managing blood glucose during Ramadan (Almansour et al, ; Gaborit et al, ; Lee et al, , ; Mygind, Kristiansen, Wittrup, & Nørgaard, ; Patel et al, ; Peterson et al, ). People with diabetes have been shown to fast despite their HCP advising against the practice (Chowdhury, Khan, Lasker, & Choudhary, ), and this was confirmed by the workshop participants when relating their experiences prior to DAFNE.…”
Section: Discussionsupporting
confidence: 78%
“…Although some participants discussed the negative aspects of fasting with diabetes, many had a positive outlook post‐DAFNE. Other studies have shown that some people with diabetes view Ramadan as an opportunity to manage their blood glucose, lose weight, and become closer to God, attributing this to the influence of religion on their beliefs and perceptions (Almansour et al, ; Gaborit et al, ; Lee et al, , ; Mygind et al, ; Patel et al, ; Peterson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, patient enrolment capacity and resources available to offer structured multidisciplinary education programs falls well below needs of the diabetes population [24]. Studies of Muslim patients living in North America, Europe, and Australia describe very low rates of information provided to them regarding overall health or specific medication management strategies during the Ramadan fast [10-12,19,20]. Pharmacists are in a unique position to serve as a source of information.…”
Section: Discussionmentioning
confidence: 99%
“…Over half (55%) of a small group of Muslim Turkish patients (n = 36) residing in Belgium were advised against fasting and over half (54%) of French general practitioners reported they discourage fasting among their diabetes patients [10,12]. Muslim diabetes patients in Australia described experiences whereby physicians failed to acknowledge the importance of participating in the Ramadan fast and therefore abandoned efforts to consult them regarding this specific care [20]. Our findings may be attributed to this being the first study in the Middle East among mostly Muslim health care providers, as well as our stratifying diabetes patients according to defined risk categories when exploring pharmacists recommendations to such patients for participating in the Ramadan fast.…”
Section: Discussionmentioning
confidence: 99%
“…Patients cite a number of reasons for choosing to fast including a sense of spiritual benefit and feeling fit enough to fast as reasons for a tradition of fasting during Ramadan. Not fasting, on the other hand, implies loss of control, a sense of isolation and stigma …”
Section: Introductionmentioning
confidence: 99%